Graphene-Based Scaffolds: Fundamentals and Applications for Cardiovascular Tissue Engineering - Savchenko, Alex; Yin, Rose T.; Kireev, Dmitry; Efimov, Igor R.; Molokanova, Elena (Frontiers in Bioengineering and Biotechnology, 2021)
Cardiac tissue engineering requires materials that can faithfully recapitulate and support the native in vivo microenvironment while providing a seamless bioelectronic interface. Current limitations of cell scaffolds include the lack of electrical conductivity and suboptimal mechanical properties. Here we discuss how the incorporation of graphene into cellular scaffolds, either alone or in combination with other materials, can affect the morphology, function, and maturation of cardiac cells. We conclude that graphene-based scaffolds hold great promise for cardiac tissue engineering.